2020
DOI: 10.1038/s41467-020-19136-7
|View full text |Cite
|
Sign up to set email alerts
|

Prime editing for functional repair in patient-derived disease models

Abstract: Prime editing is a recent genome editing technology using fusion proteins of Cas9-nickase and reverse transcriptase, that holds promise to correct the vast majority of genetic defects. Here, we develop prime editing for primary adult stem cells grown in organoid culture models. First, we generate precise in-frame deletions in the gene encoding β‐catenin (CTNNB1) that result in proliferation independent of Wnt-stimuli, mimicking a mechanism of the development of liver cancer. Moreover, prime editing functionall… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
99
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 160 publications
(116 citation statements)
references
References 30 publications
11
99
1
Order By: Relevance
“…4c, d). This highly specific editing by prime editor 3 is in line with recent results showing that off-target effects were not detectable when PE3 was used in mouse embryos 5 or human organoids 3 and is also compatible with the low frequency of off-target effects of PE3 in cultured mammalian cells 1,18 . (pOT1, .., pOT4) and those for the used sgRNA (sOT1, …, sOT4) in PE3-treated liver tissues.…”
Section: Evaluation Of Prime Editor 2 Efficiencies Using Target Sequesupporting
confidence: 88%
See 1 more Smart Citation
“…4c, d). This highly specific editing by prime editor 3 is in line with recent results showing that off-target effects were not detectable when PE3 was used in mouse embryos 5 or human organoids 3 and is also compatible with the low frequency of off-target effects of PE3 in cultured mammalian cells 1,18 . (pOT1, .., pOT4) and those for the used sgRNA (sOT1, …, sOT4) in PE3-treated liver tissues.…”
Section: Evaluation Of Prime Editor 2 Efficiencies Using Target Sequesupporting
confidence: 88%
“…Prime editing has been used in cultured mammalian cells 1,2 and organoids 3 , plants 4 , and mouse embryos 5 to introduce genetic changes in a targeted manner. However, the efficiency and precision of prime editing in postnatal mammals in vivo have not been determined.…”
mentioning
confidence: 99%
“…A study that used APOE to compare the technologies demonstrated a higher percentage of correction with the base editing approach compared to the conventional gene editing approach with less non-specific events [ 106 ]. A recent development in the CRISPR-Cas field, prime-editing [ 107 ], may offer a more precise and safe approach with much less undesired effects to correct the APOE e4 coding SNP.…”
Section: Technologies For Targeting Apoe As a Pmentioning
confidence: 99%
“…The ability to precisely install or correct pathogenic mutations regardless of their composition makes prime editing an intriguing approach to perform somatic genome editing in model organisms to study disease processes or to utilize for therapeutic applications. Previous studies have used prime editing to recode loci in cultured cells 6 , plants 7 , stem cells 8,9 , and mouse zygotes 10,11 . However, PE delivery in adult animals has not yet been described.…”
Section: Introductionmentioning
confidence: 99%